The raphe-canal diatoms (Bacillariophyceae) as a tool for paleocenological reconstructions on the shallow shelf of the Black Sea - Tymchenko, Yu.A.; Olshtynska, O.P. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2026)
Analysis of fossil diatom assemblages from Upper Pleistocene and Holocene sediments of shallow water areas of the northwestern Black Sea shelf showed the leading role of benthos in their ecological structure. A significant proportion in this autochthonous group belong to raphe-canal species of genetically close orders Surirellales and Rhopalodiales. The specific structure of the canal raphe determines the adaptation strategy and provides evolutionary advantages for existence in brackish-water biotopes of estuaries and lagoons with a muddy bottom. In the Late Quaternary assemblfges, epiphytes are found among canal-raphe diatoms, but the absolute majority belong to the epipelon, characteristic of fine-grained substrates. Cell motility contributes to free movement in search of the optimal level of light and oxygen. Changes in the taxonomic composition and ecological tolerance of raphe-canal diatoms have been traced from bottom to top along the section, showing a gradual replacement of the fresh- and brackishwater Late Pleistocene riverine and estuarine environments with early-middle Holocene brackish lagoons and modern marine conditions. The increase in the reliability and possibilities of paleoecological reconstructions on the Black Sea shelf is facilitated by the consideration of new phylogenetic data. Adaptive features of the diatom physiology and morphology are an indirect indicator of the habitat conditions and optimal growth. The nature and evolutionary relationships of a taxonomic group important for the paleoreconstruction of the shallow shelf environment contributes to increasing the reliability and new possibilities in the study of the Black Sea Late Quaternary history.